Design of Web-Based Laboratory E-Learning Information System (Case Study in UPN "Veteran" Jawa Timur Industrial Engineering’s Laboratory) - Dwi Sukma Donoriyanto; Isna Nugraha; Ario Adityawarman (International Journal of Eco-Innovation in Science and Engineering (IJEISE), 2023)
This time, the development of technology has increase rapidly, one example of technology application in education is development the concept of e-learning. However, the Industrial Management and Statistic Laboratory (IMSL) located at UPN “Veteran” Jawa Timur in the Industrial Engineering Department does not have the supporting facilities for practicum learning such as E-Learning. In other words, the learning process between laboratory assistants and practitioners is very limited, and causes a lack of intensity in interaction between laboratory assistants and practitioners. In this research, a web-based E-Learning information system will be produced to provide easiness in practicum learning for people who related to the laboratory, and can be accessed anytime and anywhere. The research method for collecting required data is by observation and interviews. This e-Learning is designed with ​​PHP, HTML, and SQL programming languages. And the supporting software that are Google Chrome, XAMPP, VSCode, and FileZilla. Based on the test results, it is concluded that the web-based IMSL E-Learning information system has provided easy learning to the practitioners and people who involved in the laboratory. While laboratory assistants can send announcements about practicum information and practitioners can do the revisions or acc reports to certain laboratory assistants systematically and online.